Soil-geomorphic surface relationships and landscape evolution in an area of the Brazilian Central Plateau - Motta, Paulo Emilio Ferreira da; Filho, Amaury de Carvalho; Ker, João Carlos; Pereira, Nilson Rendeiro; Junior, Waldir de Carvalho; Blancaneaux, Philippe (Pesquisa Agropecuaria Brasileira, 2002)
The soil-geomorphic surface relationships were investigated in an area of the Central Brazilian Plateau, based upon a high intensity reconnaissance pedological survey, aiming at the prevision of the soil attributes and their distribution in adjacent areas which don't have pedological maps. Three geomorphic surfaces, with distinctive soil distribution patterns, were identified. In the highest geomorphic surface, the soil distribution is highly related to the hydric regime variation along the hillsides, occurring Red Latosol (RL), Red-Yellow Latosol (RYL), Yellow Latosol (YL), Plinthic Yellow Latosol, Petroplinthic Yellow Latosol (PYL) (concretionary soil) and Haplic Plinthosol. These soils show very clayey texture, values of Fe2O3 and TiO2 relatively homogeneous, and Ki and Kr indexes indicatives of oxidic mineralogy. In the second surface, the soils show higher variation with respect to texture and iron and titanium contents. RL, Acricferric RL, RYL and YL are the dominant soils, with occurrence of Acriferric Endopetroplinthic RYL and YL near the borders of the high tablelands. In the third surface, that cuts the first and second ones, predominate less weathered soils, with high variable attributes, such as Haplic Cambisol, Red and Red-Yellow Argisols, Eutroferric Red Nitosol, Litholic Neosol and Fluvic Neosol. This work includes a proposition of a regional landscape evolution model.
Keywords: savannas; soil genesis; soil morphological features; geomorphology